PENERAPAN METODE SQ3R (SURVEY, QUESTION, READ, RECITE, AND REVIEW) UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MEMBACA TEXT BAHASA INGGRIS DI UNIVERSITAS ISLAM MADURA (UIM) PAMEKASAN - Supandi, Sitti Mukamilah, (Fakultas Agama Islam Universitas Islam Madura, 2018)
Language is the most important component in human life. Humans will not be able to continue their survival without language. This research was carried out at Madura Islamic University (UIM) Pamekasan due to the low ability of students, especially the Islamic Studies Faculty (FAI) in reading English text and this became the dominant problem in this study. Survey, Question, Read, Recite and Review (SQ3R) is one part of an elaboration method. A teacher expects students to be able to remember what they read, can help the teaching and learning process in the classroom carried out by reading English text so that learning can be more challenging and fun. This study uses quantitative research methods namely experimental research, the researcher will measure the effect and causality between variables X in the form of SQ3R method with variable Y, namely the ability of students to read English text at Madura Islamic University (UIM) Pamekasan. Theoretically the results of the study increased the ability of students to read English text, which is greater with a t table value of 5.356, which means that the sQ3R method can be applied in English course lectures to improve students' ability to master reading comprehension in English of Islamic Text. Students can get information faster and messages contained in text. FAI students are more confident in reading English text because English is one of the difficult subjects for Islamic faculty.